PENGARUH MEDIA SOSIAL, PENGETAHUAN INVESTASI, MOTIVASI INVESTASI DAN LITERASI KEUANGAN TERHADAP MINAT INVESTASI MAHASISWA DI PASAR MODAL : (Studi Kasus Pada Mahasiswa FEB Undana) - Laka, Estefania Bere; Rozari, Petrus E. de; Tefa, Siprianus G. (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to examine the influence of social media, investment knowledge, investment motivation and financial literacy on students' investment interest in the capital market (case study on FEB Undana students). The population in this study were active students in semester 8 in the three study programs. The research sample was 69 students obtained using purposive sampling technique. The data collection technique used a research questionnaire which was distributed through online WhatsApp groups and offline directly to students to be filled in. The data analysis technique in this study used the help of the SPSS 28 application. The results of this study indicate that the hypothesis (1) social media and hypothesis (4) financial literacy are accepted, which shows that both variables have a partial and simultaneous effect on students' investment interest. while hypothesis (2) investment knowledge and hypothesis (3) investment motivation are rejected, which means that both variables do not have a partial and simultaneous effect on investment interest. Keywords: Social Media, Investment Knowledge, Investment Motivation and Financial Literacy, Investment Interest.